Application Of Customer Service Enterprise Architecture In The Transportation Industry - Djarot Hindarto (Information Technology and Science (ITScience), 2023)
In an era of globalization and rapid technological advancements, the transportation industry is under increasing pressure to provide services that are efficient, integrated, and accommodating to the diverse requirements of customers. Enterprise Architecture is a holistic approach that can assist organizations in planning, managing, and integrating crucial elements such as business processes, information technology, data, and people. Using a qualitative approach and case studies in the transportation industry, this study investigates how the application of Enterprise Architecture can provide substantial benefits for enhancing customer service. Data was gathered by conducting in-depth interviews with various transportation organization stakeholders, including senior management, information technology personnel, and customer service teams. In the context of the transportation industry, this study seeks to analyze and describe the application of Enterprise Architecture with a concentration on customer service. The study results indicate that implementing Enterprise Architecture to customer service in the transportation industry can provide several significant benefits. Firstly, an Enterprise Architecture framework facilitates a greater comprehension of business processes and consumer interactions. This enables more effective process redesign and enhancements to customer service delivery. The author emphasizes the significance of Enterprise Architecture implementation in enhancing customer service in the transportation industry. This holistic approach can assist organizations in addressing complex challenges in a dynamic environment and provides a firm basis for customer-focused strategic decision-making. The findings of this study will likely provide valuable insights for the transportation industry and other organizations considering Enterprise Architecture implementation.